On Analysis of Banhatti Indices for Hyaluronic Acid Curcumin and Hydroxychloroquine. (31st December 2021) - Wang, Wenhu; Naeem, Muhammad; Rauf, Abdul; Riasat, Ayesha; Aslam, Adnan; Anoh Yannick, Kraidi
Abstract : Topological indices are numerical numbers assigned to the graph/structure and are useful to predict certain physical/chemical properties. In this paper, we give explicit expressions of novel Banhatti indices, namely, first K Banhatti index B 1 G, second K Banhatti index B 2 G, first K hyper-Banhatti index HB 1 G, second K hyper-Banhatti index HB 2 G, and K Banhatti harmonic index H b G for hyaluronic acid curcumin and hydroxychloroquine. The multiplicative version of these indices is also computed for these structures.